Political aspects of "buffer stock" employment: A reconsideration - Peter Kriesler; Joseph Halevi; Mark Setterfield (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2020)
Advocates of Job Guarantee (JG) or Employer of Last Resort (ELR) schemes have suggested that if the state provides "buffer stock" employment to workers displaced from private employment, then full employment can be maintained over the course of the business cycle. Kalecki was sceptical about the prospects for maintaining full employment in capitalist economies, without fundamental institutional change that would alleviate certain political constraints on the maintenance of full employment. We argue that in and of themselves, JG/ELR schemes do not create the fundamental institutional change required to address Kalecki's concerns and so ensure that full employment becomes achievable as a permanent state.
Keywords: E12; E61; J64; J68; 330; Employer of last resort; job guarantee; buffer stock employment; political aspects of full employment